The Role of m6A Regulator-Mediated Methylation Modification and Tumor Microenvironment Infiltration in Glioblastoma Multiforme - Wang, Liang; Cao, Haiyan; Zhong, Ying; Ji, Peigang; Chen, Fan (Frontiers in Cell and Developmental Biology, 2022)
N6-methyladenosine (m6A) RNA methylation is an emerging epigenetic modification in recent years and epigenetic regulation of the immune response has been demonstrated, but the potential role of m6A modification in GBM tumor microenvironment (TME) cell infiltration and stemness remain unknown. The m6A modification patterns of 310 GBM samples were comprehensively evaluated based on 21 m6A regulators, and we systematically correlated these modification patterns with TME cell infiltration characteristics and stemness characteristics. Construction of m6Ascore to quantify the m6A modification patterns of individual GBM samples using a principal component analysis algorithm. We identified 2 distinct patterns of m6A modification. The infiltration characteristics of TME cells in these 2 patterns were highly consistent with the immunophenotype of the GBM, including the immune activation differentiation pattern and the immune desert dedifferentiation pattern. We also identified 2 modes of regulation of immunity and stemness by m6A methylation. Stromal activation and lack of effective immune infiltration were observed in the high m6Ascore subtype. Pan-cancer analysis results illustrate a significant correlation between m6AScore and tumor clinical outcome, immune infiltration, and stemness. Our work reveals that m6A modifications play an important role in the development of TME and stemness diversity and complexity. Patients with a low m6AScore showed significant therapeutic advantages and clinical benefits. Assessing the m6A modification pattern of individual tumors will help enhance our knowledge of TME infiltration and stemness characteristics, contribute to the development of immunotherapeutic strategies.